Representasi Film Dystopia dan Proyeksi Akhir Zaman Perspektif Syekh Yusuf Qardhawi - Abdul Rahman Matondang; Surya Adi Sahfutra (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2022)
This study aims to analyze the representation of dystopian films and their projections towards the end of time based on Yusuf Qardhawi's perspective. The method used in this study is a qualitative method using reference tracing. The search results are analyzed based on the perspective of Sheikh Yusuf Qadhawi regarding the future and the end of time. The results of this study indicate that there is a close relationship between dystopian film representations and Syech Yusuf Qardawi's view of the end of time. These two things both show fear of the future and major changes that will occur in the future. Furthermore, dystopia films and Syech Yusuf Qardawi's views can complement each other in dealing with fears of the future and preparing for the big changes that are happening in the world At the moment.